PENGARUH KEPERCAYAAN DIRI TERHADAP AKTUALISASI DIRI MAHASISWA VOLUNTEER AYASOFYA YOUTH COMMUNITY - Diandi Nurhakim, Hilalah Zahirah, Tita Agustina, Nasichah, (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2023)
Abstract: This research is a simple linear regression quantitative research which aims to determine the influence between variable X, namely self- confidence, and variable Y, namely self-actualization of Ayasofya Youth Community volunteers. The subjects of this research are students who are active in Ayasofya Youth Community volunteer activities with age criteria of 189–22 years. The population of this study was 30 people with data collected by distributing questionnaires online via Google Form. After the data was collected, this research analysis used simple linear regression with conclusions drawn using a deductive mindset with SPSS 20 for Windows. The results of this research show that there is a positive influence on the self-confidence of Ayasofya Youth Community volunteers with the actualization of the Ayasofya Youth Community volunteers.Keywords: self-confidence, self-actualization, volunteering